Sex differences in delivery and neonatal characteristics of new-borns from the “MAMI-MED” cohort - Magnano San Lio, Roberta; Barchitta, Martina; Maugeri, Andrea; Campisi, Elisabetta; Favara, Giuliana; Granados, Claudia Ojeda; La Mastra, Claudia; La Rosa, Maria Clara; Galvani, Fabiola; Pappalardo, Elisa; Ettore, Carla; Ettore, Giuseppe; et al. (Frontiers in Public Health, 2025)
IntroductionExploring modifiable and non-modifiable determinants—like sex of new-borns, maternal characteristics, and lifestyle—of maternal and child health is a priority in Public Health. Understanding these sex-based differences is essential for tailored care and informed public health policies.MethodsThe present study aimed to delineate sex disparities in delivery and neonatal characteristics within the “MAMI MED” cohort, an ongoing prospective study involving mother–child pairs from Catania, Italy. The analysis included 1,090 mother–child pairs.ResultsThe comparison of birth weight and birth length distribution showed some differences between sexes, confirmed by higher birth weight (β = 0.121; 95% CI = 0.071–0.172) and greater birth length (β = 0.659; 95% CI = 0.360–0.958) in males compared to females. However, the comparison of small and adequate for gestational age (SGA vs. AGA) revealed that the likelihood of being SGA was higher in males than in females (OR = 1.592; 95% CI = 1.005–2.563).DiscussionThus, the focus should be on improving the assessment of gender-based differences in diagnostic criteria and incorporating gender-specific aspects into existing preventive guidelines to deeply understand the effect of gender disparities and risk factors on maternal-child health.